Strategic segmentation of customers in the market of primary real estate - Nakonechna, T.; Hryniv, N. (Lviv Politechnic Publishing House, 2017)
The authors emphasize the special significance of customer service on the primary market of residential real estate. There is carried out segmentation of the primary real estate market with the account of such a criterion as a residential housing class. There are singled out the following segments of this market: premium-segment, business-segment, comfortsegment, and economy-segment. The features of each market segment are described. An analysis of the cost of housing on the primary real estate market is carried out, depending on the readiness of the facility, namely: “foundation pit”, “foundation”, “readiness of floors”, “the gray key readiness” and the supply of housing in the primary real estate market. A detailed elaboration of strategies for cooperation with clients in the primary real estate market and strategies for establishing cooperation “client-enterprise” for certain segments of the primary real estate market are proposed. The strategy of servicing the clients of the primary real estate market according to the specifics of the product and services programmes is offered.
Keywords: segmentation; service; client; strategy; market; competitiveness; 339.14